Pengukuran Kinerja Finansial dan Non Financial dengan Pendekatan BSC Studi Kasus pada Rumah Sakit Islam Di Sumatera Barat - Adriansyah Adriansyah; Sita Fatimah Tanjung; Fitria Fitria; Riani Sukma Wijaya (Universitas Dharma Andalas, 2023)
This study aims to measure competitiveness by measuring the performance of Islamic hospitals in West Sumatra, this measurement is carried out by measuring financial and non-financial performance. The object of research at the Islamic Hospital in West Sumatra, the analysis study is the financial and non-financial reports in the form of secondary data and primary data, the data is collected using documentation techniques, review literature and interviews along with conducting field studies. The data obtained was processed and analyzed using Balance Score Card (BSC) analysis. The results showed that the Learning and Growth Perspective variable was considered good overall, but in the employee training section it was considered quite low because it was hampered by the covid-19 outbreak. In the Internal Business Process Perspective as a whole it is considered not good. whereas one of the indicators from the Customer Perspective is considered not good, namely the number of patient visits, due to the Covid-19 outbreak, even though customer satisfaction is considered good. And in the Financial Perspective on average it is considered quite good, except for accounts receivable turnover and cash ratios. Keywords: Financial Perspective; Customer; Internal Business; Learning and Growth Process ABSTRAK Penelitian ini bertujuan untuk mengukur kemampuan bersaing dengan mengukur Kinerja Rumah Sakit Islam di Sumatera Barat, pengukuran ini dilakukan dengan kinerja keuangan dan non keuangan. Objek penelitian di Rumah Sakit Islam di Sumatera Barat,kajian analisanya adalah laporan keuangan dan non keuangan berupa data sekunder dan data primer dengan, data dikumpukan dengan menggunakan teknik dokumentasi, literatur review dan wawancara beserta melakukan studi lapangan. Data yang diperoleh diolah dan dianalisa dengan menggunakan analisa Balance Score Card (BSC). Hasil penelitian menunjukkan bahwa pada variabel Perspektif Pembelajaran dan Pertumbuhan secara keseluruhan dinilai baik, namun pada bagian pelatihan karyawan dinilai cukup rendah karena terhambat oleh wabah covid-19. Pada Perspektif Proses Bisnis Internal secara keseluruhan dinilai kurang baik. sedangkan pada salah satu indikator Perspektif Pelanggan dinilai kurang baik, yaitu pada jumlah kunjungan pasien, karena adanya wabah Covid-19, meski secara kepuasan pelanggan dinilai baik. Dan pada Perspektif Finansial rata-rata dinilai cukup baik, kecuali pada perputaran piutang dan rasio kas.